1996
DOI: 10.1007/bf00395510
|View full text |Cite
|
Sign up to set email alerts
|

Fusion rate after posterior lumbar interbody fusion with carbon fiber implant: 1-year follow-up of 51 patients

Abstract: Problems associated with posterior lumbar interbody fusion (PLIF) have traditionally included the need for donor bone, prolonged healing time of donor bone, the difficulty of cutting precise bony channels, the risk of retropulsion of graft, postoperative collapse of the bone graft, and pseudarthrosis. To avoid these problems a carbon fiber reinforced polymer implant cage has been developed to facilitate interbody fusion. The aim of the present study was to evaluate the technical problems and fusion rate associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 17 publications
2
37
1
5
Order By: Relevance
“…Kuslich et al [28] reported a 91% fusion rate, 84% pain relief and 91% functional improvement at 24 months' follow-up using the BAK method of lumbar interbody fusion. Other authors [1,2,3,10,16,50,52] have reported more than 70% satisfactory clinical results with instrumented interbody fusion. Our patients had a 72% rate of clinical satisfaction with ALIF and 74% with circumferential fusion (PLIF) using subjective scores, and 79.5% and 80% clinical satisfaction using the Oswestry Disability Index.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Kuslich et al [28] reported a 91% fusion rate, 84% pain relief and 91% functional improvement at 24 months' follow-up using the BAK method of lumbar interbody fusion. Other authors [1,2,3,10,16,50,52] have reported more than 70% satisfactory clinical results with instrumented interbody fusion. Our patients had a 72% rate of clinical satisfaction with ALIF and 74% with circumferential fusion (PLIF) using subjective scores, and 79.5% and 80% clinical satisfaction using the Oswestry Disability Index.…”
Section: Discussionmentioning
confidence: 96%
“…Corticocancellous bonegrafts were used in many of these reported techniques, to achieve anterior fusion [25,30,39]. Postoperative problems like height loss, graft collapse and pseudarthrosis led to the development of carbon-fibre cages [1,52], and titanium rings [26,33] filled with cancellous grafts. The Hartshill horseshoe cage in this study achieves immediate stabilisation, and the screws in the superior and inferior vertebral bodies provide rigid fixation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the need for harvesting large amounts of autogenous iliac crest bone graft, cages have been developed that function to distract a collapsed intervertebral disc, provide immediate rigidity, and act as a structural anterior column support and bone graft carrier [39]. Unlike bone grafts, there is no risk of graft collapse leading to post-operative loss of correction and pseudarthrosis [38].…”
Section: Discussionmentioning
confidence: 99%